PENINGKATAN MANAJEMEN PEMBELAJARAN GURU MELALUI KEGIATAN PENGEMBANGAN BERKELANJUTAN GURU SMP NEGERI SE-KABUPATEN BIREUEN - marnita, MARNITA; Nurdin, Diding; Prihatin, Eka; Marwan, Marwan (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
A community service activity in the form of continuous development for teachers were carried out to improve teacher learning management in the 21st century. Continuous Professional Development (PKB) is the development of teacher competency which is carried out according to needs, in stages, on an ongoing basis. The benefit of this community service for teachers is that it provides provisions for scientific development, especially managing teacher learning in the classroom. Meanwhile, students will receive better quality learning management and be able to generate student motivation to learn effectively. The method for implementing the activities was carried out in the form of a workshop for preparing 21st century skills-oriented learning tools. The number of participants in the activity was 120 participants, divided into three groups which were held from 14-20 December 2022. From the results of implementing this activity, it was found that: 1) this activity can improve the quality of junior high school teachers' learning, as seen through the results of designing learning tools and media teach teachers, and 2) teachers are enthusiastic about participating in the activity and based on the response questionnaire, 98% of teachers hope that this activity will be sustainable. The obstacle faced in this activity was the implementation time when the school was actively studying which caused the teacher's concentration to be distracted.